'When the walls come tumbling down': The role of intergroup proximity, threat, and contact in shaping attitudes towards the removal of Northern Ireland's peace walls. (17th February 2020) - Dixon, John; Tredoux, Colin; Sturgeon, Brendan; Hocking, Bree; Davies, Gemma; Huck, Jonny; Whyatt, Duncan; Jarman, Neil; Bryan, Dominic
Abstract : Institutional structures of segregation typically entrench social inequality and sustain wider patterns of intergroup conflict and discrimination. However, initiatives to dismantle such structures may provoke resistance. Executive proposals to dismantle Northern Ireland's peace walls by 2023 provide a compelling case study of the nature of such resistance and may thus provide important clues about how it might be overcome. Drawing on a field survey conducted in north Belfast ( n = 488), this research explored the role of physical proximity, realistic and symbolic threat, and past experiences of positive and negative cross‐community contact on Catholic and Protestant residents' support for removing the walls. Structural equation modelling suggested that both forms of contact and proximity were significantly related to such support and that these relationships were partially mediated by realistic threat. It also suggested that positive contact moderated the effects of proximity. That is, for residents who had more frequent positive interactions with members of the other community, proximity to a peace wall had a weaker relationship with resistance to their removal than residents who had less frequent contact.